Comparison of the accuracy of bracket positioning between direct and digital indirect bonding techniques in the maxillary arch: a three-dimensional study - Rami Aboujaoude; Roland Kmeid; Carine Gebrael; Elie Amm (SpringerOpen, 2022)
Abstract Background/objectives When the indirect bonding technique was developed in 1972 by Silverman and Cohen, many authors wondered whether this technique would improve bracket positioning accuracy compared to the direct bonding technique. Studies have found little to no difference between them regarding positioning accuracy. Recently, technological advances have improved the indirect method by allowing the user to position the brackets virtually using software applications such as OrthoAnalyzer™. To the best of our knowledge, no studies have compared direct positioning to this new digital indirect technique. Thus, the aim of this study was to compare the accuracy of placement between the two techniques in the maxillary arch using two different bracket types: conventional twin brackets and self-ligating brackets. A secondary objective was to evaluate whether bracket type affected positioning accuracy. Methods A maxillary arch of a patient was scanned by digital impression. Forty resin duplicates of this model were printed and then mounted on a mannequin head, on which 20 practitioners performed direct bonding using the aforementioned brackets. Later on, they performed a virtual indirect bonding of the same case virtually, with the digital impression superimposed to the patient's CBCT (cone-beam computed tomography). Afterwards, the direct bonded models were unmounted, scanned, and then superimposed to the indirect models. Differences in height, angulation and mesio-distal position of the brackets were evaluated. Results Regarding height, the differences between direct and indirect methods were not significant. Height difference was significantly greater for self-ligating brackets compared to conventional brackets. Regarding mesio-distal positioning, significant differences were noted for teeth 13 and 15 with self-ligating brackets (p-value = 0.019 and p-value = 0.043, respectively). The deviation was also greater for these brackets. Regarding angulation, the difference was significant on tooth 12 when using conventional brackets (p-value = 0.04) and on 12 and 22 when using self-ligating brackets (p-value = 0.09). Conclusion/implications There were no major significant differences between direct and indirect bonding. Differences were significant only on the laterals for of angulation, and on teeth 13 and 15 for mesio-distal centering. The bracket type seems to influence positioning accuracy, since self-ligating brackets had a larger deviation range than conventional brackets.